From conventional to bioinspired: Evolution of tail surface designs in micro air vehicles - Ángel Antonio Rodríguez-Sevillano; Rafael Bardera; Estela Barroso-Barderas; Juan Carlos Matías-García; Alejandra López-Cuervo-Alcaraz (Results in Engineering)
The paper presents the evolution of the tail surface design of a micro air vehicle based on adaptive wing geometry. The initial prototype was conceived as a tailless aircraft geometry, waiting for future innovations and stability augmentations. An initial experimental test bench will be presented to characterize the variation of wing profile curvature as a function of the voltage, through MFC actuators. Once these results have been analyzed, the process of conceiving a conventional T-tail was initiated, ultimately evolving toward the proposal of a bioinspired tail based on the tail shape of various birds. The results obtained in wind tunnel tests using PIV techniques will be presented. The results validate the selected tail surface design as an appropriate geometry for a bioinspired micro air vehicle.